Management Innovation in Education: Application Case Studies Technology Learning Based Intelligence Artificial in Higher Education - Muhammad Nuzli; Bernadetha Nadeak; Marthina Mini; Atep Jejen; Nurul Rida Hardiyanti (International Journal of Educational Research Excellence (IJERE), 2023)
Managing innovation in education is key in facing the era of globalization and constant technological development. Innovation plays an important role in creating a dynamic and relevant learning environment. However, managing innovation in education is not easy, because it involves a deep understanding of various aspects, including student needs, resources, scientific developments, and social and political factors. The innovation management process includes the stages of identification, development, implementation and evaluation of innovation. The aim is to improve the quality of education, student competitiveness, efficiency and inclusiveness. However, in the real world, the introduction of innovations often encounters resistance to change, resource limitations, technological problems, and administrative barriers. In the digital era, the use of artificial intelligence (AI)-based technology in education has changed the paradigm. AI technology enables personalization of learning, efficiency, and collection of data for improvement. However, challenges include infrastructure, staff training, data privacy, and cultural change. A participatory approach, involving all stakeholders in decision-making and implementation of innovation, is an effective method in overcoming challenges and maximizing the benefits of AI technology in higher education. Both case studies underscore the importance of managing innovation and AI technology in education to improve the quality of learning, student engagement and development of relevant skills. But challenges such as infrastructure, training and privacy issues need to be addressed tactfully according to the context of each educational institution.